Economic Aspects Evaluation of Agroforestry Implementation in the Framework of Sustainable Development in Indonesia - Meidiana Mulya Ningsih; Maya Matofani; Irfianda Wahyu Arianto (Jurnal Simki Economic, 2025)
The implementation of agroforestry involves the integration of annual staple crops with various types of woody plants (and others) that provide various benefits to their users. This study attempts to evaluate the economic aspects of the implementation of agroforestry within the framework of sustainable development in Indonesia, which includes funding sources and agroforestry financing schemes, as well as the economic and environmental impacts of its implementation. The results of the study indicate that the implementation of agroforestry requires a large initial investment of 5 to 15 million rupiah per hectare. However, operational costs tend to be lower compared to monoculture farming because it allows for more efficient and sustainable land use. The implementation of agroforestry provides long-term economic benefits through increased farmer income and diversification of income sources. The impact on the environment is an efficient use of energy, improving soil quality, reducing carbon emissions, increasing productivity and land market value. The actual income from agroforestry will be felt to be greater than the potential income from carbon trading.